2008
DOI: 10.3201/eid1405.070437
|View full text |Cite
|
Sign up to set email alerts
|

Spread ofStreptococcus suisSequence Type 7, China

Abstract: Streptococcus suis sequence type (ST) 7 has been spreading throughout China. To determine events associated with its emergence, we tested 114 isolates. In all 106 ST7 strains responsible for human outbreaks and sporadic infections, the tetracycline-resistance gene, tetM, was detected on the conjugative transposon Tn 916. Horizontal transmission of tetM is suspected.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

8
81
1
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(91 citation statements)
references
References 15 publications
8
81
1
1
Order By: Relevance
“…Other studies also demonstrated that resistance to tetracycline, erythromycin and clindamycin was common in S. suis of animal origin [18,23,27]. Tetracycline resistance was found to be common among the human isolates obtained from the Chinese outbreak in 2005 [26], and 6/7 S. suis human isolates were resistant to both erythromycin and clindamycin in Japan [2]. As S. suis infection in humans is associated with exposure to pigs or contaminated pork [25], the antimicrobial susceptibility of S. suis isolated from humans might be affected by antibiotic usage during animal production.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Other studies also demonstrated that resistance to tetracycline, erythromycin and clindamycin was common in S. suis of animal origin [18,23,27]. Tetracycline resistance was found to be common among the human isolates obtained from the Chinese outbreak in 2005 [26], and 6/7 S. suis human isolates were resistant to both erythromycin and clindamycin in Japan [2]. As S. suis infection in humans is associated with exposure to pigs or contaminated pork [25], the antimicrobial susceptibility of S. suis isolated from humans might be affected by antibiotic usage during animal production.…”
Section: Discussionmentioning
confidence: 92%
“…ST1 was the major ST identified and has resulted in the deaths of 3 out of 20 patients in northern Thailand [21]. ST7 caused the human STSS outbreaks in the Sichuan and Jiangsu provinces of China [26]. Generally, CC1 was strongly associated with isolates from septicemia, meningitis, and arthritis, and is responsible for most human infections [12].…”
Section: Discussionmentioning
confidence: 99%
“…Se ha descrito también la capacidad de transmisión horizontal de material genético en transposones que codifican mecanismos de virulencia y resistencia, los que permiten la emergencia y diseminación de clones exitosos. Uno de los mecanismos de resistencia a tetraciclinas se puede transmitir de esta manera, lo que explicaría la diseminación de clones resistentes, favorecida por la utilización de estos antimicrobianos en la crianza de cerdos en China 11,16,17 .…”
Section: Discussionunclassified
“…5 Comparative analysis showed that the tetM also exists in S. suis strains from human (05ZYH33, 98HAH33 and SC84) linked to 2 outbreaks, 1,11 but is absent from the human strain GZ1 relating to sporadic infections (Table S2). 12 To predict the virulence of S. suis LSM102, its genome was screened for 15 virulence factors linked to immune evasion or systemic infection, including SalKR, NisKR, Epf, Fhb, IgA1, Ide Ssuis , MRP, Sly, Nudp, SsnA, EndA, ScpA and SsadS.…”
mentioning
confidence: 99%
“…Indeed, since the last outbreak in 2005, there has been no update on genetic diversity within S. suis and their geographic distribution in China. [4][5][6] Therefore, it is timely and meaningful to explore the genetic composition of S. suis in China, where 2 outbreaks have occurred in the past 2 decades.…”
mentioning
confidence: 99%